Small Fiber Neuropathy in Sarcoidosis - Voortman, Mareye; Raasing, Lisette; Burggraaff, Jessica; Wieske, Luuk; Veltkamp, Marcel (Seminars in Respiratory and Critical Care Medicine, 2025)
Sarcoidosis is a systemic inflammatory disorder of unknown cause, mainly affecting the lungs and lymph nodes. Symptoms are diverse and range from dyspnea and cough to fatigue, cognitive impairment, and pain. An important cause of pain in patients with sarcoidosis is small fiber neuropathy (SFN), with an estimated prevalence of 33 to 86%. The underlying pathogenesis of SFN in sarcoidosis is not known. In sarcoidosis, symptoms related to SFN can be grouped into general symptoms (e.g., fatigue), sensory symptoms (e.g., pain and numbness), and autonomic symptoms (e.g., gastrointestinal dysmotility, palpitations, or sexual dysfunction). Presentation of SFN in patients with sarcoidosis is heterogeneous and can either be length-dependent or nonlength-dependent. The small fiber neuropathy screening list assesses the frequency and severity of symptoms suggestive of SFN. As a diagnostic gold standard is lacking for SFN, the diagnosis is made on different levels of certainty based on the presence of clinical signs, normal nerve conduction studies, and either abnormal quantitative sensory testing or decreased intraepidermal nerve fiber density on skin biopsy. Autonomic dysfunction in sarcoidosis is even more difficult to diagnose, often under-recognized, and may also have a negative impact on quality of life. At present, only symptomatic relief can sometimes be achieved. While treatment of sarcoidosis usually includes corticosteroids and other immunosuppressants, these drugs are not proven effective in alleviating SFN symptoms related to sarcoidosis. This review provides an overview of symptoms, available diagnostic tools, and treatment options specific to sarcoidosis-associated SFN and autonomic dysfunction.
Keywords: sarcoidosis; small fiber neuropathy; autonomic dysfunction